Trade and Transport Corridor Management Toolkit - Kunaka, Charles (Washington, DC: World Bank, 2014)
Trade and transport corridors—major routes that facilitate the movement of people and goods between regions and between countries—have existed for millennia. They enable regions and countries to offer high-capacity transport systems and services that reduce trade and transport costs by creating economies of scale. Regional corridors are particularly important to landlocked countries, often providing the only overland routes to regional and international markets.